2019
DOI: 10.1155/2019/2824017
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Genetic Identification of Three Entamoeba Species in Pigs in Southeastern China

Abstract: Parasitic Entamoeba spp. can infect many classes of vertebrates including humans and pigs. Entamoeba suis and zoonotic Entamoeba polecki have been identified in pigs, and swine are implicated as potential reservoirs for Entamoeba histolytica. However, the prevalence of Entamoeba spp. in pigs in southeastern China has not been reported. In this study, 668 fecal samples collected from 6 different regions in Fujian Province, southeastern China, were analyzed to identify three Entamoeba species by nested PCR and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(41 citation statements)
references
References 28 publications
3
34
3
1
Order By: Relevance
“…There are no published studies on fasciolopsis in Rwanda, but it is a food-borne infection, and humans develop it after they eat raw aquatic vegetation or food plants contaminated with metacercariae [ 33 ]. Pigs can develop amoebiasis due to Entamoeba suis and E. polecki , and the latter one is a zoonotic species [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are no published studies on fasciolopsis in Rwanda, but it is a food-borne infection, and humans develop it after they eat raw aquatic vegetation or food plants contaminated with metacercariae [ 33 ]. Pigs can develop amoebiasis due to Entamoeba suis and E. polecki , and the latter one is a zoonotic species [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, there was no evidence of Entamoeba suis-specific DNA in the samples. E. suis was observed in 81.1% samples from pigs sampled in West Java, Indonesia [66], while Ji et al observed a considerable lower positive rate (13.0%) for E. suis in pigs sampled in south-eastern China [65]. To our knowledge, E. suis is yet to be reported and confirmed at DNA-level in Europe.…”
Section: Discussionmentioning
confidence: 76%
“…polecki was divided into four specific subtypes by Verweij et al in 2001 [64], all of which have been isolated from human stool, but which appear to differ in terms of host reservoir specificity. Of these four subtypes, ST1 and ST3 appear to be common in pigs [16,63,65,66]. Meanwhile ST4 has only been found in humans so far, whereas ST2 has been found in non-human primates as well.…”
Section: Discussionmentioning
confidence: 99%
“…The genus Entamoeba includes a variety of anaerobic, unicellular, and monoxenic protozoan species adapted to live as parasites or commensals in the digestive tracts of humans and a large variety of animals of different classes [ 5 , 7 , 64 , 110 , 112 , 205 , 206 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Entamoeba spp. have a variety of vertebrate hosts: E. moshkovskii is found in cattle, elephants, and reptiles [ 94 , 110 ]; E. coli and E. hartmanni are found in non-human primates [ 26 , 57 , 113 , 220 ]; and finally, some studies suggest that different subtypes of E. polecki , infect human, non-human primates, pigs and ostriches [ 41 , 59 , 76 , 84 , 112 ].…”
Section: Introductionmentioning
confidence: 99%